Measuring Global Poverty Right: Mission Impossible? - Quibria, M. G. (Institutional Knowledge at Singapore Management University, 2006)
The international community is committed to millennium development goals which postulate a vision of global development that makes eliminating poverty and sustaining development the overriding objective of global development efforts. In the hierarchy of the MDGs, the first and foremost goal is to reduce by half, between 1990–2015, the proportion of people whose income is less than a dollar a day (a widely used yardstick to measure extreme poverty). However, estimating such poverty across developing countries and globally is by no means a simple exercise nor has it yielded unambiguous results. This article provides a brief summary of the state of the art in global poverty estimates, including the problems as well as the possible solutions.